IPTEKS PENGENDALIAN INTERNAL DALAM MEMINIMALKAN RESIKO KREDIT BERMASALAH PADA LEMBAGA PEMBIAYAAN - Clarisa, Saskya; Tangkuman, Steven J. (Universitas Sam Ratulangi, 2018)
PT. FIFGROUP as a company engaged in financing services is a company whose main source of profit comes from interest on community loans. Therefore the main problem that is often faced for a finance company is bad credit, which is where consumers do not smoothly make installment payments that cause losses, so that the company must think hard to reduce the credit risk so that the company's operational activities can run well. Therefore the internal control system at the company is very important, especially in terms of internal control of credit. The purpose of this study is to find out the internal controls that are applied in the company through the process of credit submission by consumers to billing to minimize credit risk.Keyword : internal control, credit risk